Glycoprotein IIb/IIIa inhibitors use in the setting of primary percutaneous coronary intervention for ST elevation myocardial infarction in patients pre‐treated with newer P2Y12 inhibitors. Issue 8 (11th June 2021) - Blanchart, Katrien; Heudel, Thibaut; Ardouin, Pierre; Lemaitre, Adrien; Briet, Clément; Bignon, Mathieu; Sabatier, Rémi; Legallois, Damien; Roule, Vincent; Beygui, Farzin
Abstract: Objectives: We sought to investigate the safety and potential benefit of administrating glycoprotein IIb‐IIIa inhibitors (GPIs) on top of more potent P2Y12 inhibitors. Background: A number of clinical trials, performed at a time when pretreatment and potent platelet inhibition was not part of routine clinical practice, have documented clinical benefits of GPI in ST‐segment elevation myocardial infarction (STEMI) patients at the cost of a higher risk of bleeding. Methods: We used the data of a prospective, ongoing registry of patients admitted for STEMI in our center. For the purpose of this study only patients presenting for primary percutaneous coronary intervention and pretreated with new P2Y12 inhibitors (prasugrel or ticagrelor) were included. We compared patients who received GPI with those who did not. Results: Eight hundred twenty‐four STEMI patients were included in our registry; GPIs were used in 338 patients (41%). GPI patients presented more often with cardiogenic shock and Thrombolysis in myocardial infarction (TIMI) flow grade <3. GPI use was not associated with an increase in in‐hospital or 3‐month mortality. Bleeding endpoints were similar in both groups. Conclusions: Our study suggests that GPI may be used safely in combination with recent P2Y12 inhibitors in STEMI patients in association with modern primary percutaneous coronary intervention strategies (radial access and anticoagulation with enoxaparin) with similar bleeding and mortality rates at hospital discharge and 3‐month follow‐up.